Conservation status of three rare endemic Phaseolus bean (Leguminosae, Phaseoleae) species of Costa Rica - Debouck, Daniel; Chaves Barrantes, Néstor; Araya Villalobos, Rodolfo (Wiley, 2024)
We aimed at an inventory of all populations of wild Phaseolus (bean) species in Costa Rica, in relation to future plant breeding. During the field work in 2003–2018, three new and rare bean species (i.e. P. albicarminus , P. angucianae and P. hygrophilus ) were found in different montane forest habitats which originally occupy a small acreage. Field observations, together with satellite images, indicate deforestation due to coffee plantations or pastures. To date only eleven populations of these species are known, distributed along the Talamanca and Fila Cruces mountainous ranges, making them endemic. Their narrow distribution, deforestation affecting the original habitats, and occurrence outside established and enforced protected areas motivate the assessment of their conservation status as ‘Endangered' (EN).